The Culture of Consumerism in Advertising: An Analysis of the Representation of Social Values through Mass Media - Vannyora Okditazeini; Oktri Permata Lani Permata Lani; Marhen Marhen; Fadhilatul Khaira (Asian Journal of Media and Culture, 2025)
This study examines the role of advertising in shaping social perceptions and reinforcing existing social inequalities in society. In an increasingly digitally connected context, advertising functions not only as a tool for promoting products but also as a cultural force that influences public views on gender, social class, race, and ethnicity. This literature review aims to analyze how advertising creates, strengthens, or even challenges social stereotypes and prevailing norms. Based on a literature review methodology, this research collects and analyzes various relevant academic literatures, including journals, books, and articles that discuss the impact of advertising on social perceptions across different cultural and geographical contexts. The findings show that advertising often reinforces traditional gender stereotypes, portrays social class in a reductive manner, and strengthens racial hierarchies in society. However, on the other hand, there are also efforts to challenge these stereotypes through more inclusive advertising campaigns, such as femvertising. This study also highlights how social media is increasingly playing an important role in shaping narratives about social status and consumer identity. Overall, the findings suggest that advertising not only reflects but also shapes social values and norms, thus having a significant impact on the formation of social inequalities. This research is expected to provide insights for the development of more ethical and diversity-oriented advertising policies and practices